Strategies in Expressing Gratitude Performed by English Department Students in 5 th th and 7 Semester of Different Gender: A Socio-Pragmatics Approach - Arrum, Regita Sekar (Jurnal Bahasa, Sastra, dan Studi Amerika, 2022)
In this study, the researcher focuses on the analysis of the strategies in expressing gratitude performed by English Department students in 5th and 7th semester of different genders. The objectives of this study are (1) identifying the contexts, types, and functions that influence gratitude expression uttered by the 5th and 7th semester of English Department students based on gender differences, (2) analyzing and discovering the language pattern in gratitude expression used by the 5th and 7th semesters of English Department students based on gender differences. The researcher uses a descriptive-qualitative method and employed Spradley’s analysis method in collecting and analyzing the data which includes domain, taxonomic, componential and cultural theme analysis. The source of data is in the form of participants; the students of 5th and 7th semester in English Department whereas the data were taken from responses in the form of utterances in DCT answered by the participants. Throughout the taxonomic analysis, the data were classified using Cheng’s taxonomy (2005) of gratitude strategies. The findings show that (1) each of the different situational contexts hooked the respondents to employ different gratitude expression whether it is male or female students, (2) both male students in the 5th   and 7th   semesters have a similar pattern to each other in expressing gratitude as well as female students in the 5th and 7th semester. The researcher also found similarities and dissimilarities in gratitude expression patterns used by male students and female students.